PENGEMBANGAN MOBILE LEARNING MODULE BERBASIS ANDROID PADA PEMBELAJARAN PPKN TINGKAT SMP - Prasetyo, Gunawan Langgeng; Abduh, Mohamad; Rumiati, Sri (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
This study aims to produce an Android-based mobile learning module product that meets the feasibility and effectiveness tests in improving digital literacy skills and understanding of national diversity of junior high school students in the subject of Civics. The module was developed using the ADDIE model involving 2 material experts and 1 media expert as well as 60 eighth grade junior high school students divided into a control class and an experimental class. The validation results from material and media experts indicate that the product is classified as very feasible, with a final score exceeding 87% in all aspects, especially in digital literacy development, interactivity, and content effectiveness. Meanwhile, the results of the effectiveness test through a quasi-experimental design showed a significant increase in two main variables: digital literacy (N-Gain = 0.441) and understanding of national diversity (N-Gain = 0.555), both in the moderate category. The testpaired sample t-teststrengthens this finding with a significance value of 0.000 (<0.05). Thus,Mobile Learning Module This has proven to be suitable and effective for use as a digital learning medium that supports the implementation of the Independent Curriculum, strengthens 21st-century competencies, and encourages the internalization of the values of national diversity in students. ABSTRAKPenelitian ini bertujuan untuk menghasilkan produk mobile learning module berbasis android yang memenuhi uji layakan serta efektivitas dalam meningkatkan kemampuan literasi digital dan pemahaman kebinekaan bangsa siswa SMP pada mata pelajaran PPKn. Modul dikembangkan menggunakan model ADDIE dengan melibatkan 2 pakar materi dan 1 pakar media serta 60 siswa kelas VIII SMP yang terbagi dalam kelas kontrol dan kelas eksperimen. Hasil validasi dari pakar materi dan media menunjukkan bahwa produk tergolong sangat layak, dengan skor akhir melebihi 87% pada seluruh aspek, terutama pada pengembangan literasi digital, interaktivitas, dan efektivitas konten. Sementara itu, hasil uji efektivitas melalui desain eksperimen semu menunjukkan adanya peningkatan signifikan pada dua variabel utama: literasi digital (N-Gain = 0,441) dan pemahaman kebinekaan bangsa (N-Gain = 0,555), keduanya dalam kategori sedang. Uji paired sample t-test memperkuat temuan ini dengan nilai signifikansi 0,000 (<0,05). Dengan demikian, Mobile Learning Module ini terbukti layak dan efektif digunakan sebagai media pembelajaran digital yang mendukung implementasi Kurikulum Merdeka, memperkuat kompetensi abad ke-21, serta mendorong internalisasi nilai-nilai kebinekaan bangsa dalam diri peserta didik.